2015
DOI: 10.3892/or.2015.3717
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant hirudin suppresses the viability, adhesion, migration and invasion of Hep-2 human laryngeal cancer cells

Abstract: Abstract. Recombinant hirudin (rH) is a highly potent and specific inhibitor of thrombin, and has been shown to inhibit the growth and metastasis of several types of cancers in experimental tumor models. The objective of this study was to evaluate the antitumor effects and explore the underlying mechanisms of rH in Hep-2 human laryngeal carcinoma (LC) cells. Hep-2 cells were treated with various concentrations of rH for 24 h. The cell viability was evaluated by a water-soluble tetrazolium salt (WST) assay. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Remarkably, rH significantly down-regulated the expression of proteins FAK and VEGF-R, suggesting that the anti-tumor effect of rH might be associated with the suppression of angiogenesis by down-regulating the VEGF/VEGF-R pathway. (Lu et al, 2015). These findings also suggested that targeting thrombin by rH is a potential strategy for treating LC.…”
Section: Vegf/vegf-rmentioning
confidence: 85%
“…Remarkably, rH significantly down-regulated the expression of proteins FAK and VEGF-R, suggesting that the anti-tumor effect of rH might be associated with the suppression of angiogenesis by down-regulating the VEGF/VEGF-R pathway. (Lu et al, 2015). These findings also suggested that targeting thrombin by rH is a potential strategy for treating LC.…”
Section: Vegf/vegf-rmentioning
confidence: 85%
“…As non-invasive and inexpensive tests, they are suitable for initial screening or use in combination with other biomarkers for certain types of cancer diagnosis or prevention. Moreover, recombinant hirudin, an inhibitor of thrombin to prevent the formation of fibrinogen and d dimer, has been reported to inhibit the growth and metastasis in several types of cancer cells [62,63]. Based on the fact that the binding sites of fibrinogen with immune cells are different from its coagulation cascade recognition sites, it is an ideal target for pharmacological intervention without affecting its coagulation functions [64].…”
Section: Discussionmentioning
confidence: 99%
“…Hirudin inhibited TCIPA in non-small-cell lung cancer cell lines (NSCLC) and in SCLC, but in the last case, blocking TCIPA required addition of the ADP scavenger apyrase with hirudin [ 60 ]. Recombinant hirudin (rH) has also been shown to inhibit growth and exert anti-metastatic effects in several types of cancers through multiple mechanisms [ 185 , 188 ]. Experimental studies with laryngeal carcinoma cells (HEp-2 cells) demonstrated that rH inhibited the adhesion, migration, and invasion of the cancer cells.…”
Section: Thrombin Inhibitorsmentioning
confidence: 99%